2020
DOI: 10.5603/gp.2020.0005
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of eleven commonly used formulae for sonographic estimation of fetal weight in prediction of actual birth weight

Abstract: Objectives: The aim of the study is to compare the accuracy of 11 formulas in predicting fetal weight. Material and methods: The study includes 1072 pregnant women of gestational age from 28 to 42 weeks, who gave birth between January and June 2017. Pregnant women were divided into five groups; group 1, where actual birth weight (ABW) was less than 2500 g, group 2, where ABW was between 2500-4000 g, group 3, where ABW was above 4000 g. Group 4-newborns with birth weight under 10 percentile and group 5-newborns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…However, 10–15 % errors in estimated foetal weight v . actual weight are not uncommon and may be attributed to high inter- and intra-observer variability in biometric measurements, the choice of equation and the amplification of errors in single parameters when included in a calculation ( 28 , 38 42 ) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 10–15 % errors in estimated foetal weight v . actual weight are not uncommon and may be attributed to high inter- and intra-observer variability in biometric measurements, the choice of equation and the amplification of errors in single parameters when included in a calculation ( 28 , 38 42 ) .…”
Section: Resultsmentioning
confidence: 99%
“…(2) References/standards: -Serial measurements can be plotted on same growth charts as individual biometric measurements -Various methods to quantify growth velocity (44) (including individualised growth charts (2)), but none are widely implemented in practice Cut-offs: Delphi Consensus Statement for FGR* includes downward crossing of more than two quartiles (43) Foetal body composition Ultrasonography: -Subcutaneous fat thickness -Organ size Gestational age-related Foetal body composition is not routinely assessed, and no universally acknowledged references/standards or cutoffs exist; organ size measurements may be used to assess foetal health conditions (38) *Delphi Consensus Statement for Foetal Growth Restriction (43) International Fetal and Newborn Growth Consortium for the 21st Century (INTERGROWTH-21st) (34) . However, 10-15 % errors in estimated foetal weight v. actual weight are not uncommon and may be attributed to high inter-and intra-observer variability in biometric measurements, the choice of equation and the amplification of errors in single parameters when included in a calculation (28,(38)(39)(40)(41)(42) . The aim of foetal growth assessment is the detection of FGR or excessive foetal growth.…”
Section: Antenatal Period: Foetal Growth Assessmentmentioning
confidence: 99%
“…Many factors affect the accuracy of the assessment, including the abnormal fetus, large deviation in data collection of AC and HC, and difficulty in obtaining accurate measurement section due to examination conditions in late pregnancy. Plonka et al [31] showed that fetuses with different conditions should be assessed with different formulas. Dimassi et al [32] showed that ultrasound examination in the delivery room was reasonable, but the accuracy rate of EFW was only 62.1%.…”
Section: Discussionmentioning
confidence: 99%
“…stimation of Fetal Weight (EFW) is an essential key in the decision-making process for obstetric planning and management [1,2]. Assessment of fetal weight is an essential part of predicting fetal weight disorders that include intrauterine growth disorders (weight less than 10% relative to gestational age) and macrosomia (weight more than 90% relative to gestational age) [3,4]. To prevent the fetal, neonatal, and maternal morbidities and mortalities associated with Intrauterine Growth Retardation (IUGR) and macrosomia neonates, accurate estimation of fetal weight is very important [5].…”
Section: Introductionmentioning
confidence: 99%